Sexualidade e gênero: atividades pedagógico-culturais na educação infantil - CORRÊA, Isabella dos Santos (2019)
Gender and sexuality issues are treated as a great taboo in childhood, for many think of the child as an asexual being who has no sexuality. By doing so, one ends up reproducing culturally constructed standards, leaving aside the construction of the subjectivity of the child, as well as repressing his discoveries about his own body. Given this, the present work intends to analyze how the issues of gender and sexuality in Child Education have been worked on, trying to identify the role of the teacher in the sexual formation of the child, as well as their qualification to deal with situations that involve the object of study. The theoretical reference counts as the theoretical contribution of the authors, Louro (1997), Escolano (1998), Felipe (2012), Scott (1995), Xavier Filha (2012), among others. To obtain the results will be used the qualitative approach, especially ethnography, having as analytical tools the observation, the conversations and the application of questionnaires, which will allow to study the quotidian of the relations of gender and sexuality in a kindergarten. The results indicate that the school influences the sexual formation of the child guiding their behaviors and educating according to the gender norm, as well as that teachers are not fully prepared to face the manifestations of sexuality in childhood. It is concluded that it is necessary for the school to appropriate the various possibilities of working gender and sexuality in children's education, with tranquility and without prejudice, being aware that such matters are necessary in the formation of the child.